2020
DOI: 10.1177/2325967120939001
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Augmentation of Engineered Tendon-Fibrocartilage-Bone Composite With Acellular Dermal Graft Using Double Rip-Stop Technique for Canine Rotator Cuff Repair

Abstract: Background: The retear rate after rotator cuff repair remains unacceptably high. Various biological engineered scaffolds have been proposed to reduce the retear rate. We have developed a double rip-stop repair with medial row knot (DRSK) technique to enhance suture-tendon strength and a novel engineered tendon-fibrocartilage-bone composite (TFBC) for rotator cuff repair. Hypothesis: DRSK rotator cuff repair augmented with TFBC will have better biomechanical properties than that of DRSK repair with an acellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The etiology of enthesis degeneration represents an important gap in knowledge, particularly the understanding of cellular mechanisms that are required for robust healing and for the development of evidence‐based therapeutic strategies. Many biologic and engineering therapeutic strategies have been proposed for rotator cuff enthesis healing and regeneration; 46 however, animal model research has largely been focused on juvenile and young animals rather than mature or aged animals, which is a substantial weakness given that age‐associated changes are not present in these model systems. It is important to note that during aging systemic and local changes occur including increased accumulation of senescent cells within tissues and systemic increases in sterile inflammation, also termed inflammation, which compromise the ability of tissue to repair and regenerate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The etiology of enthesis degeneration represents an important gap in knowledge, particularly the understanding of cellular mechanisms that are required for robust healing and for the development of evidence‐based therapeutic strategies. Many biologic and engineering therapeutic strategies have been proposed for rotator cuff enthesis healing and regeneration; 46 however, animal model research has largely been focused on juvenile and young animals rather than mature or aged animals, which is a substantial weakness given that age‐associated changes are not present in these model systems. It is important to note that during aging systemic and local changes occur including increased accumulation of senescent cells within tissues and systemic increases in sterile inflammation, also termed inflammation, which compromise the ability of tissue to repair and regenerate.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45] The etiology of enthesis degeneration represents an important gap in knowledge, particularly the understanding of cellular mechanisms that are required for robust healing and for the development of evidence-based therapeutic strategies. Many biologic and engineering therapeutic strategies have been proposed for rotator cuff enthesis healing and regeneration; 46 F I G U R E 6 Tenogenic potential of RCECs in different ages. RCECs from different-age groups were successfully differentiated into tenocytes lineage under inducement.…”
Section: Long Et Al | 1887mentioning
confidence: 99%
“…Cadaveric biomechanical studies have shown greater load to failure and less repair displacement with graft augmentation. 6 Clinical studies have demonstrated the clinical benefit of graft augmentation as well. A recent randomized control trial by Avanzi et al 7 comparing single-row repairs with and without porcine dermal allograft augmentation in small-and medium-sized tears showed a clear benefit to graft augmentation.…”
Section: See Related Article On Page 2342mentioning
confidence: 99%